(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2024)
Thinking habits can be cultivated through habits of mind (HoM), shaping pre-service teachers’ analytical, reflective, and decision-making skills essential for Education for Sustainable Development (ESD). This study examines HoM proficiency among 99 pre-service biology teachers using closed- and open-ended questionnaires and curriculum analysis. More than half of pre-service biology teachers scored moderately, indicating a need for habits of mind improvement. The findings offer educators, curriculum developers, and policymakers insights into designing strategies to strengthen HoM, ensuring teachers can integrate sustainability concepts into education, a task of significant urgency and importance. By fostering critical inquiry, problem-solving, and lifelong learning, prospective teachers will better prepare students to address the global sustainability challenge.